Mendorong Kemampuan Membaca Siswa Sekolah Dasar melalui Intervensi Fonik - Husnul Chotimah, Duhita Laksmi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
The advancement of the nation is determined by human capital quality, one of which is basic literacy (reading). The ability to read is one of the important skills that children must learn during the first years of elementary school (Mujis & Reynolds, 2008). Nevertheless, the problem of reading development has yet become a problem in various area in Indonesia. This study uses an experiment method with single subject research design. The aim of the study was to develop and determine the effectiveness of the phonic intervention model for elementary school students who have difficulty reading and writing. The phonic intervention model in this study was developed based on an assessment of the participants. The intervention was composed of a series of structured verbal instructions propped with reading aids. The results showed that the phonic intervention could improve children's reading skills if applied consistently. The interventions that supported by conducive environment can effectively help the development of reading skills in elementary school students.